Perencanaan dan Pengendalian Bahan Baku Pendukung Guna Mengoptimalkan Persediaan dan Meminimasi Biaya Persediaannya pada PT. XYZ - Nekea, Keane Kenze; Mundari, Siti (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
PT. XYZ is a manufacturing company engaged in processing raw paper materials. The paper is processed into finished products such as release liners, label stickers, and digital printing media. PT XYZ faces challenges in managing its raw material inventory, particularly for the packaging support materials. The company offers 66 types of products, several of which require specific raw materials, and the demand for each product varies and is not consistent. To address this issue, inventory control methods such as Fixed Order Interval (FOI) and Min-Max can be applied. These methods help determine the optimal quantity of raw material procurement and minimize inventory costs. Based on the calculations, the FOI method resulted in the lowest total inventory cost, amounting to IDR 128,748,345, compared to the company’s current policy, which amounts to IDR 137,694,671. The difference in total inventory cost between the FOI method and the company’s policy is IDR 8,946,326, or approximately 6.5% lower.